Modeling commuter mode shift to electric railway services: an integrated performance analysis and stated preference approach for the Rangkasbitung – Merak line - Gineung Pratidina; Muhammad Oka Mahendra (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2026)
This study investigates the relationship between railway travel service characteristics and passenger demand on the Rangkasbitung – Merak commuter rail corridor. Secondary data on passenger volumes were obtained from PT Kereta Commuter Indonesia, while primary data were collected via on-board surveys conducted across multiple afternoon trips. Descriptive statistical analyses were performed to determine key performance indicators—namely load factor, travel time, dwell time, and commercial speed against established service standards. Subsequently, a binary logistic regression model was employed to assess the influence of travel cost and travel time on passengers’ likelihood to choose electric commuter services over conventional local trains. Results reveal an average load factor of 2.40, indicating the existing service capacity is frequently exceeded during peak periods. Average dwell times ranged between 2–5 minutes per station, and observed commercial speeds fell below the stipulated benchmark. Logistic regression analysis showed that travel cost (p = 0.316) did not exert a statistically significant effect on mode choice, whereas travel time emerged as a significant determinant: improvements in travel time increased the probability of passengers opting for electric commuter services by approximately 72.1%. These findings suggest that enhancing operational speed and optimizing station dwell times are critical to meeting passenger demand and improving overall service attractiveness on the Rangkasbitung – Merak route.